So vetrne elektrarne problematičen projekt? - Golobič, Mojca (Urbani izziv, 2005)
In the post-transition period the system and its actors haven't adjusted accordingly, despite the fairly long and successful practise of planning and decision-making concerning physical development. While sailing such stormy seas and avoiding the Scylla of technocracy and Charydbis of corporativism, everything gets tossed around, once one way, the other, the next, and there isno evidence of approaching quiet waters of professionally supported participative decision-making. Planning and decision-making nevertheless have a key role in the creation of acceptable or problematic projects. The article uses the example of the quest and identification for a site for wind generators in Slovenia to illustrate the condition's symptom. Following analyses of the applied harmonisation and argumentation methods in various decision-making forms, the weaknesses of professional-technocratic and consultative-corporativistic approaches and informal public debates are shown,as well as the advantages and possibilities enabled by the applied methods in the quest for concordant solutions.
Keywords: elektrarne; prostorski razvoj; Slovenia; Slovenija; urejanje prostora; veter